2004
DOI: 10.1200/jco.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Tumor-Positive Nonsentinel Lymph Nodes After Tumor-Positive Sentinel Lymph Node Dissection for Melanoma

Abstract: Thicker primary and larger SN tumor size are factors that correlate best with tumor-positive NSN. Although none of these factors are absolutely predictive of residual nodal disease, these factors must be strongly considered if the SN contains metastasis, as they provide enhanced risk assessment for NSN tumor-positivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(93 citation statements)
references
References 36 publications
4
81
0
8
Order By: Relevance
“…In our experience, the number of positive SLNs was not associated to an increasing NSLN involvement, whilst the prognostic relevance of Starz classification was ascertained in univariate but not confirmed in multivariate logistic regression analysis. The predictive value of Breslow thickness on NSLN involvement has been found in some previous papers, but not confirmed by others [10], [13], [14], [15], [20], [31] and [33]; the same happens for ulceration, thus confirming a great deal of variability which limits the drawing of definite conclusions. Some studies suggested also to consider the association of two or more variables.…”
Section: Discussionmentioning
confidence: 89%
“…In our experience, the number of positive SLNs was not associated to an increasing NSLN involvement, whilst the prognostic relevance of Starz classification was ascertained in univariate but not confirmed in multivariate logistic regression analysis. The predictive value of Breslow thickness on NSLN involvement has been found in some previous papers, but not confirmed by others [10], [13], [14], [15], [20], [31] and [33]; the same happens for ulceration, thus confirming a great deal of variability which limits the drawing of definite conclusions. Some studies suggested also to consider the association of two or more variables.…”
Section: Discussionmentioning
confidence: 89%
“…In a study conducted by Morton et al (2006), a 5-year survival rate of 72% was seen in patients with positive sentinel lymph nodes, followed by immediate lymph node dissection, whereas patients undergoing a delayed lymph node dissection had a 5-year survival rate of only 52%. However, further positive non-sentinel lymph nodes are found in a relatively small proportion of patients: previously quoted figures ranged from 17%-24% (Ghaferi et al, 2009;Lee et al, 2004;Rossi et al, 2008;Wright et al, 2010). However, a recent study has shown rates of further positive findings to be as low as 14.8% (Kunte et al, 2011).…”
Section: Elective Regional Lymph Node Dissectionmentioning
confidence: 82%
“…This has prompted several authors to try to identify patients at low risk of harboring additional microscopically evident disease in the nonsentinel lymph nodes. 104,105 The experience of Wagner et al, as published in Cancer, has been representative; most investigators have had difficulty reliably predicting which patients may safely avoid a lymph node dissection. 106 These reports have cemented the completion lymph node dissection as the standard of care when a patient has a positive sentinel lymph node, at least for now.…”
Section: Surgical Treatment Of Melanomamentioning
confidence: 99%